Valuing Stakeholder Governance: Property Rights, Community Mobilization, and Firm Value - Dorobantu, Sinziana; Odziemkowska, Kate (Strategic Management Journal, 2017)
Research summary : While research has shown that good stakeholder relations increase the value of a firm, less is known about how specific types of stakeholder governance affect firm value. We examine the value of one such governance mechanism—community benefits agreements ( CBA s) signed by firms and local communities—intended to minimize social conflict that disrupts access to valuable resources. We argue that shareholders evaluate more positively CBA s with local communities with strong property rights and histories of institutional action and extra‐institutional mobilization because these communities are more likely to cause costly disruptions and delays for a firm. We evaluate these arguments by analyzing the cumulative abnormal returns associated with the unexpected announcement of 148 CBA s signed between mining companies and local indigenous communities in Canada. Managerial summary : With firms across many industries facing escalating costs associated with social conflict, new tools are emerging to help firms mitigate these risks by seeking the support of the local communities in which they operate. Community benefits agreements ( CBA s) are contracts in which a community provides consent for a new investment in return for tangible benefits, such as local hiring and revenue sharing. We argue that although CBA s are costly for the firm, they are particularly valuable when communities can cause costly disruptions and delays for a firm. Our study of investor reactions to the announcement of 148 CBA s signed between mining companies and local indigenous communities in Canada shows that investors value more CBA s signed with communities with strong property rights and histories of protest . Copyright © 2017 John Wiley & Sons, Ltd.